Program Literasi Digital bagi Anak-Anak Kampung Wonopuro, Dusun Sidowayah, Kabupaten Ponorogo: Digital Literacy Program for Children in Kampung Wonopuro, Dusun Sidowayah, Ponorogo Regency - Maruti, Endang Sri; Isticomah, Binti; Yustiwa, Galuh Mei; Khoiru, Ulifa; Huda, Nur (LP2M INSURI Ponorogo, 2021)
Children in their education are among those are most affected during the Covid-19 pandemic because they have to study at home online while teachers have never held home visits to monitor student learning processes directly. As a result, many children cannot learn optimally. This program aims to help children to improve their digital literacy skills and also make it easier for parents to guide and monitor their children's activities. For this reason, this program is carried out as an effort for Digital Literacy for isolated village children in Kampung Wonopuro, Dusun Sidowayah, Ponorogo Regency of East Java Province, so that they can continue to live life like children in other advanced villages. The program has resulted that it can improve digital literacy for the participating children. From the social side, children's enthusiasm for learning to develop their potential and achievements in the midst of the current pandemic is highly discoverable; while from a psychological point of view, it can help increase the learning motivation of the children in Kampung Wonopuro. Anak-anak dalam pendidikannya termasuk yang paling terdampak di masa pandemi Covid-19 karena harus belajar di rumah secara online sedangkan guru tidak pernah melakukan kunjungan rumah untuk memantau proses belajar siswa secara langsung. Akibatnya banyak anak yang tidak bisa belajar secara maksimal. Program ini bertujuan untuk membantu anak-anak meningkatkan kemampuan literasi digitalnya dan juga memudahkan orang tua dalam membimbing dan memantau aktivitas anaknya. Untuk itu, program ini dilakukan sebagai upaya Literasi Digital bagi anak-anak desa terpencil di Kampung Wonopuro, Dusun Sidowayah, Kabupaten Ponorogo Provinsi Jawa Timur, agar mereka dapat terus menjalani kehidupan seperti anak-anak di desa maju lainnya. Program tersebut telah menghasilkan dapat meningkatkan literasi digital bagi anak-anak peserta. Dari sisi sosial, semangat belajar anak untuk mengembangkan potensi dan prestasinya di tengah pandemi saat ini sangat terlihat; sedangkan dari segi psikologis dapat membantu meningkatkan motivasi belajar anak-anak di Kampung Wonopuro.